Efektifitas Pelaksanaan Pembelajaran Pendidikan Jasmani Olahraga dan Kesehatan di Madrasah Tsanawiyah Persis 96 Garut - Syahrul Ardiyansyah; Abduloh Abduloh; Nana Suryana Nasution (Jurnal Literasi Olahraga, 2020)
Abstract This studi aims to determine the Effectiviness implementation proses of physical education and sport education in Madrasah Tsanawiyah Persis 96 sub district of Garut district. The problem of this research is to find out how the process of implementing physical education and sport education that takes in Madrasah Tsanawiyah Persis 96 Garut. This research is a qualitive descriptive study, which illustrates how implementation of physical education and sport education in Madrasah Tsanawiyah Persis 96 Garut, the subjects in this study were four students, one physical teacher. Data collection techniques used ini this study were observation, interviews, and documentation. Data analysis techniques used in this study are reduction and data display techniques. The results showed that the implementation of physical education and health ini Madrasah Tsanawiyah Persis 96 Garut in terms of prepation was quitegood. While in the school facilites and infrastructure ti meet the learning process of physical education, because the physical education teacher who is not a graduate of the physical education profession teacher must further develop his knowledgein physical education learning. Keywords : Effectiviness Implementation of Physical Education Learning.